Environmental Awareness as a Mediator: Understanding the Relationship Between Community Attachment and Green Consumption in Lembah Harau Nature Park - Heksa Putera Eksa; Lilik Wahyudi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research comprehensively examines the mediating role of environmental awareness in the relationship between the three dimensions of community attachment (affective attachment, place dependence, and place identity) and green consumption behavior within the vulnerable ecosystem of Lembah Harau Nature Park, West Sumatera. Amid escalating global environmental concerns, fostering sustainable consumption is imperative in natural destinations. Employing a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a robust sample of 262 respondents (comprising tourists and local residents), this study unveils critical insights into the underlying psychological mechanisms. The results indicate that affective attachment and place dependence significantly and positively influence environmental awareness. Crucially, environmental awareness subsequently serves as the sole, potent full mediator, confirming its pivotal role as the primary catalyst for responsible consumption. Specifically, emotional and functional bonds to Lembah Harau translate into green consumption behavior exclusively through heightened environmental awareness. Conversely, place identity surprisingly demonstrated no significant effect on either environmental awareness or green consumption in this context. These findings underscore that while emotional and functional attachments form a necessary foundation, cognitive environmental awareness is the central mechanism that drives sustainable behavior. Practical implications for destination managers and policymakers highlight the necessity of prioritizing effective, targeted environmental awareness strategies to actively promote sustainable tourism practices in Lembah Harau, extending beyond the mere cultivation of passive place attachment.